THE STATUS OF THE LAW OF MEMORANDUM OF UNDERSTANDING REVIEWED FROM ALL THE LEGAL AGREEMENTS IN CODE OF CIVIL LAW - Siti Syarifah Wafiqah Wardah; Ma’ruf Hafidz; Abdul Qahar (P3M Stia Al Gazali Barru and Meraja media, 2020)
[Full Paper] to pdf Copyright (c) 2020 Meraja journal